Impact of Government Regulation on Microfinance - Hubka, Ashley; Zaidi, Rida (Washington, DC: World Bank, 2012)
Microfinance has demonstrated success as a poverty reduction strategy, but the critical challenge now is to make microfinance sustainable and ubiquitous. By increasing microfinance' s scope (number of individuals reached), impact (effect on well-being of borrowers), depth (ability to reach the poorest of the poor) and the number of financial products, it can be made available not just to the moderate poor at whom it has traditionally been targeted, but also to the extreme poor and the vulnerable non-poor. Bringing about this change in the scale will require the commercialization of microfinance, with MFIs transforming themselves into formal financial institutions, and a shift in the nature and degree of government involvement. Governments can encourage sustainable, market-based microfinance by: 1) eliminating unfair competition from public institutions; 2) undertaking regulatory reform; and 3) improving the business environment.